Polarization control of metal-enhanced fluorescence in hybrid assemblies of photosynthetic complexes and gold nanorods - Bujak, Lukasz; Olejnik, M.; Brotosudarmo, T. H. P.; Schmidt, M. K.; Czechowski, Nikodem; Piatkowski, Dawid; Aizpurua, Javier; Cogdell, R. J.; Heisse, W.; Mackowski, Sebastian (Physical Chemistry Chemical Physics, 2014)
Fluorescence imaging of hybrid nanostructures composed of a bacterial light-harvesting complex LH2 and Au nanorods with controlled coupling strength is employed to study the spectral dependence of the plasmon-induced fluorescence enhancement. Perfect matching of the plasmon resonances in the nanorods with the absorption bands of the LH2 complexes facilitates a direct comparison of the enhancement factors for longitudinal and transverse plasmon frequencies of the nanorods. We find that the fluorescence enhancement due to excitation of longitudinal resonance can be up to five-fold stronger than for the transverse one. We attribute this result, which is important for designing plasmonic functional systems, to a very different distribution of the enhancement of the electric field due to the excitation of the two characteristic plasmon modes in nanorods. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-07